Individual behavior, culture, and social change - Glenn, Sigrid S. (2004)
The principle of operant selection is examined as a prototype of cultural selection, and the role of the social environment is suggested as the critical element in the emergence of cultural phenomena. Operant contingencies are compared to cultural selection contingencies, designated as metacontingencies. Both of these types of contingency relations result in evolving lineages of recurrences that can become increasingly complex in the number and organization of their elements. In addition to its role in the recurring interlocking behavioral contingencies that constitute cultural organization, operant behavior plays another role in cultures. Although the operants of individuals are functionally independent of one another, the behavior of each person may contribute to a cumulative effect that is relevant to the well-being of many people. Similarly, the outcomes of metacontingencies may also contribute to a cumulative effect. The relation between independently evolving operant lineages, or between independently evolving cultural lineages, and their cumulative effect is identified as a macrocontingency. Macrocontingencies do not involve cultural-level selection per se. Effective cultural engineering requires identifying the macrocontingencies that produce less than desirable effects and altering the relevant operant contingencies or metacontingencies to produce change in the cumulative effects.